Attenuation by HSP90 inhibitors of EGF-elicited migration of osteoblasts: involvement of p44/p42 MAP kinase. (4th July 2022) - Kuroyanagi, Gen; Kawabata, Tetsu; Tokuda, Haruhiko; Fujita, Kazuhiko; Matsushima-Nishiwaki, Rie; Sakai, Go; Tachi, Junko; Hioki, Tomoyuki; Kim, Woo; Iida, Hiroki; Otsuka, Takanobu; Kozawa, Osamu
ABSTRACT: Background: We have demonstrated that epidermal growth factor (EGF)-induced migration of osteoblast-like MC3T3-E1 cells is mediated through p44/p42 mitogen-activated protein (MAP) kinase, p38 MAP kinase, stress-activated protein kinase/ c- Jun N-terminal kinase (SAPK/JNK), and Akt.The molecular chaperone heat shock protein 90 (HSP90) is abundantly expressed in osteoblasts. However, the role of HSP90 in osteoblast migration remains obscure. Objective: In this study, we investigated the effect of HSP90 inhibitors on the EGF-induced migration of MC3T3-E1 cells and the mechanism. Methods: Clonal osteoblast-like MC3T3-E1 cells were treated with the HSP90 inhibitors geldanamycin or onalespib and then stimulated with EGF. Cell migration was evaluated using the transwell cell migration assay and wound-healing assay. The viability of MC3T3-E1 cells was analyzed using the Cell Counting Kit-8. The phosphorylation of p44/p42 MAP kinase, p38 MAP kinase, SAPK/JNK, Akt, and protein kinase-like endoplasmic reticulum kinase (PERK) was evaluated by western blot analysis. Results: EGF-induced migration was significantly suppressed by geldanamycin and onalespib, evaluated by both transwell cell migration assay and wound-healing assay. Geldanamycin and onalespib did not significantly alter cell viability. Geldanamycin and onalespib markedly reduced the EGF-induced phosphorylation of p44/p42 MAP kinase, but not p38 MAP kinase or Akt. By contrast, geldanamycin and onalespib increased the EGF-induced phosphorylation of SAPK/JNK. PERK phosphorylation was not significantly affected by geldanamycin or onalespib. Conclusion: Our results strongly suggest that HSP90 inhibitors reduce the EGF-induced osteoblast migration through the p44/p42 MAP kinase.